2012
DOI: 10.1371/journal.pone.0040826
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Assembles into Structured Filamentous Virion Particles Independently of Host Cytoskeleton and Related Proteins

Abstract: Respiratory syncytial virus (RSV) is a single-stranded RNA virus that assembles into viral filaments at the cell surface. Virus assembly often depends on the ability of a virus to use host proteins to accomplish viral tasks. Since the fusion protein cytoplasmic tail (FCT) is critical for viral filamentous assembly, we hypothesized that host proteins important for viral assembly may be recruited by the FCT. Using a yeast two-hybrid screen, we found that filamin A interacted with FCT, and mammalian cell experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 41 publications
3
33
0
1
Order By: Relevance
“…A role of actin and myosin in the transport of the viral ribonucleoprotein (RNP) complex has also been described previously, and the role of the ARP2/3 complex in the terminal stage of virus budding and in the process of pinching off from the cell surface has been proposed [6]. Conversely, a previous study showed that F protein trafficking to the cell surface and assembly of RSV filaments appeared to take place even when cytoskeleton rearrangement is blocked by actin inhibitors [45]. Our results suggest that efficient RSV budding indeed depends on functional ARP2/3 nucleation and actin rearrangement.…”
Section: Discussionmentioning
confidence: 96%
“…A role of actin and myosin in the transport of the viral ribonucleoprotein (RNP) complex has also been described previously, and the role of the ARP2/3 complex in the terminal stage of virus budding and in the process of pinching off from the cell surface has been proposed [6]. Conversely, a previous study showed that F protein trafficking to the cell surface and assembly of RSV filaments appeared to take place even when cytoskeleton rearrangement is blocked by actin inhibitors [45]. Our results suggest that efficient RSV budding indeed depends on functional ARP2/3 nucleation and actin rearrangement.…”
Section: Discussionmentioning
confidence: 96%
“…Structural information of the CT and the targets with which it may interact will be required to understand this differential impact. A candidate for interaction is filamin-A, which was recently identified in a yeast two-hybrid screen of a lung cDNA library using CT peptide as bait (17). The second most influential region was CT-R1, with a maximum decrease in infectivity of 85%.…”
Section: Discussionmentioning
confidence: 99%
“…F is critically involved in entry steps, such as attachment and membrane fusion (14)(15)(16), and also plays a role in viral assembly (3,4,17). Using a virus lacking the F protein CT, we previously demonstrated that the CT plays a role in F protein distribution and membrane fusion function and is critical for the production of infectious progeny (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We know from previous work that the M protein and the F protein cytoplasmic tail (CT) are important in the organization of virion assembly (5,24,(33)(34)(35). M is a nonglycosylated phosphorylated protein of 256 amino acids (36)(37)(38).…”
mentioning
confidence: 99%